The effect of creatine monohydrate supplementation during combined strength and high intensity training on performance in rowers - Bell, G. J.; Syrotuik, D.; Game, A.; Gillies, E. (1999)
There was a significant interaction effect for body mass indicating that the Cr group gained 0.7 kg over the 5 day loading period. Five days of Cr loading did not change body composition (% fat, lean body mass) nor did it improve repeated interval rowing performance, 2000 m rowing performance or repeated strength performance greater than the placebo group. Ventilation threshold, maximal oxygen consumption, 2000 m rowing performance time, repeated interval performance and repeated 10 RM strength significantly increased similarly in both groups after 5 weeks of combined training. The ability to perform more repetitions per set of strength exercise for bench press and leg press after 5 weeks of training was also not greater with Cr supplementation. Also, the ability to maintain power output during repeated 250 m and 500 m high intensity intervals during training was not significantly greater with Cr supplementation compared to placebo.